Multilingual, multicultural Europe and criminal law : Parental child abduction - a case study - Forbes, Joana; Maia, Belinda (Language and Law / Linguagem e Direito, 2016)
The European Directive 2010/64/EU on the right to interpretation and translation in criminal proceedings should have been in force by 2014 in all EU countries, and it will further exacerbate the existing problems of finding people to provide effective interlingual and intercultural communication, especially in cases where cultural norms differ, as in the case of family law. Despite the efforts to homogenize European systems, much legal language continues to be used and interpreted according to local cultural norms, even when there is some agreement as to the legal terminology at a more general European level. In this paper we focus on criminal cases involving family problems such as cases of minors who have been abducted and taken to another country by one parent, without the consent of the other. We shall trace the cultural and terminological dificulties faced by all concerned during the legal process. Ultimately, this research aims to contribute to the perception of the diculties in applying the European Directive 2010/64/EU at the everyday level demanded by the agents of the law, many of whom have little perception of legal systems or cultures outside their own and share the general public’s lack of awareness of the nature of translation.